2004
DOI: 10.1128/mcb.24.7.2890-2904.2004
|View full text |Cite
|
Sign up to set email alerts
|

Translocation Products in Acute Myeloid Leukemia Activate the Wnt Signaling Pathway in Hematopoietic Cells

Abstract: The acute myeloid leukemia (AML)-associated translocation products AML1-ETO, PML-retinoic acid receptor alpha (RAR␣), and PLZF-RAR␣ encode aberrant transcription factors. Several lines of evidence suggest similar pathogenetic mechanisms for these fusion proteins. We used high-density oligonucleotide arrays to identify shared target genes in inducibly transfected U937 cells expressing AML1-ETO, PML-RAR␣, or PLZF-RAR␣. All three fusion proteins significantly repressed the expression of 38 genes and induced the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
277
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 277 publications
(294 citation statements)
references
References 55 publications
13
277
1
2
Order By: Relevance
“…13 Although most of these related studies reported that the Groucho/TLE family of corepressors inhibits gene expression and the signaling pathway, it also enhances the gene expression including the macrophage colony stimulating factor receptor, 14 Notch ligand Jagged1, 15 and Wnt pathway mediator plakoglobin. 16 The Groucho/ TLE family of corepressors was also suggested to be an oncogene because the over-expression of Gro/TLE family members is associated with lung adenocarcinoma, 17 grade 1 astrocytomas, 18 higher-grade meningiomas, 19 pituitary adenomas, 20,21 and synovial sarcomas, 7,22 which is consistent with our results.…”
Section: Discussionsupporting
confidence: 81%
“…13 Although most of these related studies reported that the Groucho/TLE family of corepressors inhibits gene expression and the signaling pathway, it also enhances the gene expression including the macrophage colony stimulating factor receptor, 14 Notch ligand Jagged1, 15 and Wnt pathway mediator plakoglobin. 16 The Groucho/ TLE family of corepressors was also suggested to be an oncogene because the over-expression of Gro/TLE family members is associated with lung adenocarcinoma, 17 grade 1 astrocytomas, 18 higher-grade meningiomas, 19 pituitary adenomas, 20,21 and synovial sarcomas, 7,22 which is consistent with our results.…”
Section: Discussionsupporting
confidence: 81%
“…Jagged upregulation triggered activation of the Notch pathway, and primary AML blasts with t(8;21) showed expression of the Notch target gene HES1. In a similar U937-based inducible system, Muller-Tidow and colleagues identified Plakoglobin as a target gene activated by AML1-ETO [21]. This upregulation occurred through direct transcriptional activation of the Plakoglobin promoter by AML1-ETO, a unique example of promoter activation by a putative transcriptional repressor.…”
Section: Challenges To the Classical Model: Gene Expression Profilesmentioning
confidence: 99%
“…Other reports indicate involvement of Wnt signaling in AML, CLL and multiple myeloma. [108][109][110][111] Studies on ALL are conspicuously absent, except for one report showing that the E2A-PBX1 fusion protein, involved in certain types of precursor B-ALL, activates the expression of Wnt16. 112 But studies with patient material and comparisons with normal precursor B cells (which undergo Wnt signaling) are lacking.…”
Section: Wnt In T-cell Leukemiamentioning
confidence: 99%